Educational Transitions in War and Refugee Contexts: Youth Biographies in Afghanistan and Austria - Thoma, Nadja (2022)
This article addresses educational transitions under conditions of multiple insecurities. By analyzing empirical data of two research projects with youths in Afghanistan and refugee students in Austria, we show how young peoplemake sense of the social and educational inequalities they encounter on their educational pathways within different national, socio‐political, and institutional contexts. We present in‐depth analyses of two cases to elaborate how young people in different parts of the world conceive of their futures when basic security needs are not met, and how they make sense of the social and educational inequalities they face during their transition processes. After living through repeatedly fractured perspectives, young people have to make sense of their biographical experiences and continuously (re)design their plans while facing uncertain futures. In the Afghan Youth Project, we reconstructed a collective—and morally charged—biographical orientation of future plans. This orientation can also be understood as a critical response to persistent fragility and inequality and suggests an imagined generational hold and sense of belonging. In the Austrian project Translating Wor(l)ds, we reconstructed continuing experiences of educational exclusion, marginalization, and devaluation in different migration societies throughout refugee routes. Educational transitions, which can be challenging for all young people, take on special relevance under these conditions. Combining biographical and socio‐psychological research perspectives allows us to reconstruct educational processes as cumulative, non‐linear processes and to reveal the ambiguities, contradictions, and ruptures woven into them, as well as the subjects’ constructions of sense and agency.